1997
DOI: 10.1063/1.531856
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical approach to inverse scattering for the Dirac equation

Abstract: Solution of the Dirac equation with pseudospin symmetry for a new harmonic oscillatory ring-shaped noncentral potential J. Math. Phys. 53, 082104 (2012) Effect of tensor interaction in the Dirac-attractive radial problem under pseudospin symmetry limit J. Math. Phys. 53, 082101 (2012) Asymptotic stability of small gap solitons in nonlinear Dirac equations J. Math. Phys. 53, 073705 (2012) On Dirac-Coulomb problem in (2+1) dimensional space-time and path integral quantization J. Math. Phys. 53, 063503 (2012) Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 5 publications
(6 reference statements)
1
26
0
Order By: Relevance
“…Similar results for non-obstacle relativistic-scattering are presented in [8,28]. There error bounds are not provided and a different class of (bounded) electromagnetic potentials is addressed.…”
Section: High-momenta Limit Of the Scattering Operatorsupporting
confidence: 48%
See 1 more Smart Citation
“…Similar results for non-obstacle relativistic-scattering are presented in [8,28]. There error bounds are not provided and a different class of (bounded) electromagnetic potentials is addressed.…”
Section: High-momenta Limit Of the Scattering Operatorsupporting
confidence: 48%
“…In [3] and [31] one can see that the circulation of the magnetic potential appears on the leading order term of the high velocity asymptotic of the scattering operator, whereas the contribution of the electric potential appears only on the second order term (see [31] for related issues). For relativistic equations in the whole space, see [8] and [28]. The time dependent methods for inverse scattering that we use are introduced in [9], for the Schrödinger equation.…”
Section: Introductionmentioning
confidence: 99%
“…This method can be used to study Hamiltonians with electric and magnetic potentials [1], the Dirac equation [21] and Stark Hamiltonians [31,27].…”
Section: The Main Results and The Strategy Of The Proofmentioning
confidence: 99%
“…The strategy we adopt to prove our main result is based on a high-energy asymptotic expansion of the scattering operator S. Such a technique was introduced by Enss and Weder in [11] and used sucessfully to recover the potential of multidimensional Schrödinger operators (note that the case of multidimensional Dirac operators in flat spacetime was treated later by Jung in [21]). They showed that the first term of the high-energy asymptotics is exactly the Radon transform of the potential they are looking for.…”
Section: Introductionmentioning
confidence: 99%
“…This method can be used to study Hamiltonians with electric and magnetic potentials on L 2 (R n ) [1], the Dirac equation [9], the N-body case [4], the Stark effect ( [15], [17]), the AharonovBohm effect [18].…”
Section: The High Energy Limit Of the Scattering Operatorsmentioning
confidence: 99%